Open government and citizenempowerment in authoritarian states - Kurmanov, B.; Knox, C. (Journal of Eurasian Studies, Vol. 13(2),156–171, 2022)
The introduction of open government has been used in many countries to improve the transparency, accountability of the state, and promote participation by citizens in collaborative governance. Its potential for public services improvement, citizen empowerment, and a positive impact on reducing corruption have attracted scholarly attention. Set alongside this, open government initiatives have facilitated greater access to information which can be used to hold governments to account and, in so doing, build trust between citizens and the state. While open government principles sit easily in democratic systems, some authoritarian states have also adopted this concept. This raises two questions. First, is there evidence that open collaboration, as the most developed form of open government, has empowered citizens in autocracies? Second, and more generally, why would authoritarian regimes seek to adopt open government when the concepts of autocracy and openness are antithetical? This paper attempts to address these questions using three case study countries in Central Asia: Kazakhstan, Uzbekistan, and Kyrgyzstan which adopted open government policies. It finds evidence of co- optation, network authoritarianism, and state unresponsiveness/resistance to citizens’ inputs.
Keywords: Open government, citizens’ empowerment, authoritarianism, Central Asia